Infak dan Peningkatan Ekonomi : Kajian Interdisipliner Al-Qur’an dan Al-Hadis dengan Bidang Ekonomi - Zaky Mubarok; Syamsurizal Yazid (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Zakat, infaq, and alms are forms of charity that are part of the worship of Muslims, especially infaq is seen as an important tool to increase social solidarity and create economic justice. This study aims to identify and analyze the role of infaq in strengthening the community's economy from the study of the Qur'an and Hadith. The method used in this study is library research, using a qualitative approach. The data sources used are the Qur'an, Hadiths, books and journals related to the theme for the validity of the data presented. The results of the study show that based on a cross-disciplinary study involving the perspective of the Qur'an, Hadith, and economics, infaq that is carried out voluntarily without coercion has a positive impact on economic growth, both at the individual level and at the macro social level.